An escalating continuum of learning and attention difficulties from premutation to full mutation in female carriers of FMR1 expansion - Gabis, Lidia V.; Shaham, Meirav; Attia, Odelia Leon; Kowal, Tamar; David, Sivan; Banet-Levi, Yonit; Shefer, Shahar; Gabis, Daniel; Mula-Topf, Dana; Avrech Bar, Michal; Bart, Orit; Segal, Osnat (Frontiers in Neurology, 2023)
Objective Carriers of Fragile X premutation may have associated medical comorbidities, such as Fragile X-associated tremor and ataxia (FXTAS) and Fragile X-associated premature ovarian insufficiency (FXPOI). We examined the Fragile X premutation effect on cognition, and we assumed that there is a direct correlation between the continuous spectrum of specific learning and attention deficits to the number of CGG repeats on the FMR1 gene. Methods A total of 108 women were referred to our center due to a related Fragile X syndrome (FXS) patient, 79 women carried a premutation of 56–199 repeats, and 19 women carried a full mutation of more than 200 CGG repeats on FMR1 gene. Genetic results of CGG repeats, demographic information, structured questionnaires for ADHD, learning disabilities of language and mathematics, and independence level were analyzed in women carrying the FMR1 premutation and compared to the group carrying the full mutation. Women with FXS and FXTAS were excluded. Results When analyzed as a continuum, there was a significant increase in the following complaints which were associated with a higher number of repeats: specific daily function skills such as driving a car, writing checks, disorientation in directions, and also specific learning difficulties such as spelling and math difficulties. Additionally, when tested as a categorical independent variable, we observe that women with the full mutation were more likely to have ADHD or other learning disability diagnoses in the past than during premutation (<200 CGG repetitions). Conclusion Specific learning and attention difficulties and resulting daily function difficulties correlate with an increased number of CGG repeats and are more likely to be associated as a common feature of premutation and full mutation in a female premutation carrier. Despite evidence of learning and attention difficulties, it is encouraging that most female carriers of the premutation and full mutation function well in most areas. Nevertheless, they face significant difficulties in specific areas of functioning such as driving, and confusion in times and schedules. Those daily function skills are mostly impacted by dyscalculia, right and left disorientation, and attention difficulties. This may aid to design specific interventions to address specific learning deficits in order to improve daily function skills and quality of life.